2022
DOI: 10.1038/s41598-022-14610-2
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive bioinformatics analysis to identify potential prognostic biomarkers among CC and CXC chemokines in breast cancer

Abstract: Breast cancer (BC) is a major human health problem due to its increasing incidence and mortality rate. CC and CXC chemokines are associated with tumorigenesis and the progression of many cancers. Since the prognostic values of CC and CXC families' expression in various types of cancers are becoming increasingly evident, we aimed to conduct a comprehensive bioinformatics analysis elucidating the prognostic values of the CC and CXC families in BC. Therefore, TCGA, UALCAN, Kaplan–Meier plotter, bc-GenExMiner, cBi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 101 publications
3
38
0
Order By: Relevance
“…In the current study, we found that ZNF639 knockdown increased the expression of CCL20 and downstream phosphorylation of AKT and STAT3. CCL20 is one of the C-C and C-X-C chemokines that correlate with the clinical outcomes of breast cancer patients [22]. Our ndings are in agreement with others showing that CCL20 induces epithelial-mesenchymal transition with upregulation of vimentin and Snail1 in breast epithelial cells through the PI3K/AKT and JAK2/STAT3 pathways [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we found that ZNF639 knockdown increased the expression of CCL20 and downstream phosphorylation of AKT and STAT3. CCL20 is one of the C-C and C-X-C chemokines that correlate with the clinical outcomes of breast cancer patients [22]. Our ndings are in agreement with others showing that CCL20 induces epithelial-mesenchymal transition with upregulation of vimentin and Snail1 in breast epithelial cells through the PI3K/AKT and JAK2/STAT3 pathways [23,24].…”
Section: Discussionsupporting
confidence: 91%
“…CXCL9 has been proved to be a good prognostic biomarker for many tumors. Hozhabri et al found higher levels of CXCL9 in breast cancer patients with higher SBR grade; furthermore, high CXCL9 expression levels were signi cantly associated with lymphocytic in ltration and better response to chemotherapy in breast cancer patients [32] . In the present study, a joint database analysis showed that CXCL9 presented high expression in EC.…”
Section: Discussionmentioning
confidence: 98%
“…-In the triple-negative (TNBC) subtype of breast cancer, higher levels of CCL5 than in non-TNBC are pointed out (Hozhabri, Moghaddam, Moghaddam, & Mohammadian, 2022).…”
Section: C-c Motif Chemokine Ligand 5 (Ccl5)mentioning
confidence: 99%
“…Chen et al, 2020). A shorter OS and RFS are recorded in low-expressed CCL21 BC patients, which is proposed to increase immunogenicity (Hozhabri et al, 2022). In conjunction with CCL19, CCL21 is documented to take a vital part in establishing a bridge between dendritic cells and naïve T cells and activates TH1-polarized immunogenicity (Nguyen-Hoai et al, 2016).…”
Section: C-c Motif Chemokine Ligand 21 (Ccl21)mentioning
confidence: 99%
See 1 more Smart Citation